Volterra operator from Bergman spaces to Morrey spaces - Wu, Xingling; Wu, Zhijian (Eurasian Mathematical Journal, 2013)
We characterize the boundedness of Volterra operators from Bergman spaces to Morrey spaces. Tools in the holomorphic function spaces, properties of Carleson measures and the atomic decomposition for functions in Bergman spaces are heavily employed.